Indonesia's economic and environmental resilience in the face of climate change: Analysis and implementation strategies - Wurarah, Rully Novie (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Backgorund: Climate change is a significant threat to Indonesia, an archipelago that is vulnerable to the negative impacts of this phenomenon. This study aims to identify the effects of climate change in Indonesia and evaluate mitigation and adaptation strategies needed to improve economic and environmental resilience. Based on climate change projections, increases in surface temperature, changes in rainfall patterns, sea level rise, and changes in water salinity have negative impacts on various sectors such as agriculture, fisheries, infrastructure, and public health. Method: The research method includes secondary data analysis from various official sources and a study of relevant literature, with an analytical descriptive approach to identify critical challenges and necessary strategies. Findings: The results show that limited fiscal space and the need for budgetary reform are significant challenges that need to be addressed through the introduction of a carbon tax, budgetary incentives for green technologies, and the removal of fossil fuel subsidies. In addition, mobilization of non-budget funding sources is needed to support green projects, with strategies such as the development of public-private partnerships, access to international funds, and technical capacity building. Conclusion: In conclusion, implementation of the recommended mitigation and adaptation strategies can increase Indonesia's resilience to climate change, reduce its risks and negative impacts, and ensure the sustainability of economic and social development. Novelty/Originality of this study: This research provides practical guidance for policymakers to develop effective strategies to deal with climate change